2021
DOI: 10.3917/geco1.143.0013
|View full text |Cite
|
Sign up to set email alerts
|

Quand Amour et Argent doivent rimer au quotidien… Un agenda de recherche sur la gestion des finances au sein des couples

Abstract: La recherche en comportement du consommateur revête souvent une dimension individuelle, ignorant ainsi la dynamique décisionnelle liée à la gestion des finances au sein du couple. Cette dynamique apparait pourtant comme essentielle dans l’explication des décisions de consommation des ménages. À l’heure actuelle, seulement un nombre réduit de travaux de recherche s’est penché sur cette problématique, un constat d’autant plus vrai lorsque l’on s’intéresse à la littérature française. Cet article propose une revue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The harmony characterizing the relationship of ethical couples is in line with previous research, which found that happy partners try to find integrative solutions and buy less often on their own [48,51]. The agreement to purchase ethical products is associated with syncratic decision, which consists of a joint decision made by couples who choose to buy ethical products [75].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The harmony characterizing the relationship of ethical couples is in line with previous research, which found that happy partners try to find integrative solutions and buy less often on their own [48,51]. The agreement to purchase ethical products is associated with syncratic decision, which consists of a joint decision made by couples who choose to buy ethical products [75].…”
Section: Discussionsupporting
confidence: 81%
“…The outcome of the interaction process can be explained by an unequal distribution of the balance of power in favor of the less ethical partner. According to resource theory, the balance of power is determined by the comparative resources of both partners [51], for instance, in terms of education, income, or competence. The more powerful partner (here, the less ethical partner) uses her/his superior role, and the less powerful partner (here, the more ethical partner) is expected to let it go.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations